Prokaryotic Transposable Elements - Varani, Alessandro M. [UNESP]; Ross, Karen E.; Chandler, Mick (My University, 2024)
Prokaryotes have provided an abundance of transposable elements (TEs), which have greatly contributed to our present understanding of the importance of TE in remodeling their host genomes and regulating gene expression, and have been key to our present understanding of transposition mechanism(s) and its regulation. It has now been over 40 years since the first bacterial insertion sequences (ISs), arguably the simplest autonomous prokaryotic TE, were described. There are a limited number of transposase types based on the chemical reactions they catalyze during strand cleavage, and they are often named after key amino acids in their catalytic sites. These include DDE, HUH and enzymes resembling the site-specific tyrosine and serine recombinases. Apart from IS-derived compound transposons, there are only a limited number of transposon families based on their distinct sets of transposition-related genes and DNA, features such as the end sequences and recombination sites.